Diagnostic utility of reticulocyte hemoglobin for iron-restricted anemia in patients with end-stage kidney disease on hemodialysis - Almashjary, Majed N.; Sahl, Ammar M.; Hazzazi, Mohannad S.; Alhashmi, Mohammad H.; Bawazir, Waleed M.; Basabrain, Ammar A.; Borai, Anwar; Khalil, Haitham; Almohammadi, Mohammad; Altayar, Malik A.; Alqarni, Abdullah M.; Jamalallail, Sahl A.; et al. (Frontiers in Medicine, 2025)
BackgroundChronic kidney disease (CKD) is a serious, long-term illness that damages kidneys and lowers glomerular filtration rate. CKD often causes anemia. Iron deficiency (ID) is common in these patients and worsens illness symptoms. Modern hematology analysers can measure reticulocyte mean cell hemoglobin (MCHr), which directly measures iron integration into erythrocyte hemoglobin. MCHr can improve iron deficiency detection in CKD patients, who have aberrant iron indicators due to chronic inflammation. This research aims to evaluate the effectiveness of MCHr as a marker for ID in patients with CKD.MethodTo obtain data for this study, CBC, reticulocyte profile, and iron biomarkers were collected from King Khalid National Guard Hospital (Ref No. IRB/1861/23). Transferring saturation was calculated using (Serum iron/TIBC) × 100. GraphPad Prism 9 software was used to analyze the data, and Mann-Whitney, Spearman correlation, and ROC plots were used to determine MCHr's diagnostic performance. A p-value < 0.05 was considered significant.ResultThe study compared 190 individuals undergoing hemodialysis (HD) with 165 healthy blood donors. The HD group showed lower levels of RBC, Hb, MCHr, serum iron, and total iron-binding capacity (TIBC). Despite anemia, the HD group had higher levels of ferritin and transferrin saturation (TSAT). MCHr demonstrated excellent diagnostic performance in identifying iron deficiency anemia (IDA), particularly in functional iron deficiency. When TSAT was < 20%, MCHr showed an AUC of 0.98, with 100% specificity and 72.41% sensitivity, significantly outperforming ferritin and TSAT in inflammatory settings. In the HD group with ferritin levels < 200 ng/mL, the MCHr cut-off value of < 31.20 pg had a sensitivity and specificity of 89.47% and an AUC of 0.89. When TSAT was < 20%, the MCHr cut-off value of < 23.95 pg had a sensitivity of 72.41%, specificity of 100%, and AUC of 0.98.ConclusionsBased on the findings, MCHr is more effective than ferritin and TSAT in detecting iron deficiency in hemodialysis patients. Future research should use MCH to investigate the impact of iron therapy with or without rHuEPO.